Exploring the Algerian Novel-the Colonial Legacy -the Post-Colonial Discourse Nexus. Themes and Languages - BOUDERSA, Hemza; BOUGHERARA, Khemissi (Journal of Human Sciences, 2020)
Initial findings of the paper show that the Algerian novel in French had even a key role after the independence of the country. Some novels served as a means to ‘liberate’ the Algerian mind from remnants of the colonial legacy. The Algerian novelists, therefore, through their literary works showed ‘demystifying’, ‘revealing’ and ‘therapeutic’ roles;  ‘demystifying’ clouds of history,  ‘revealing’ horrors of the colonizer and looked for ‘curing’ the ills of the colonizer's legacy. It also plays an explicit role in portraying the ‘force’ used by the colonizer to unveil the ‘false’ reasons behind that colonialism. Thus, the pertinent recommendation drawn from this paper is that the post-colonial discourse brought a new ‘memory war’ in which the Algerian novel in French should take a position to reconstruct the Algerian ‘distorted’ and ‘clouded’ memory. Glorifying genuine history and debunking the ‘‘false’ are the two main aspects of this role.